Risk of premature cardiovascular disease and all-cause mortality in young adults, association with risk factor prevalence early in life - Chenrui Zhu; Liuxin Li; Mingchen Zhao; Jie Li; Haibo Gao; Huiying Li; Yan Liu; Chunpeng Ji; Zhe Huang (BMC Cardiovascular Disorders)
Abstract Background With the increase in risk factors and the emergence of unhealthy lifestyles in young adults, we need to pay more attention to the cardiovascular health of this group. This study aimed to assess the association of the degree of joint risk factor control with premature cardiovascular disease (CVD) and all-cause mortality in young people. Methods Kailuan Study is a prospective cohort study based on a community population, which began in June 2006, and followed up every two years. A sample of 16,519 eligible participants in the Kailuan cohort was recruited in this current study and 15,948 was included in the final analysis, with an average age of 32.34 ± 5.19 years, and a male proportion of 74.76%. Based on the control status of the risk factors, participants were divided into three groups: well-controlled group (≥ 7 risk factors controlled), moderately controlled group (5–6 risk factors controlled), and poorly controlled group (≤ 4 risk factors controlled). Multivariate Cox proportional hazard model was used to analyse the relationship between the joint control of risk factors and onset of CVD and all-cause mortality. Results During a mean follow-up period of 14.78 ± 1.33 years, we identified 285 incident CVD cases and a total of 274 deaths from all causes. Compared to the well-controlled group, the moderately controlled group and poorly controlled group exhibited progressively higher risks of CVD and all-cause mortality. The adjusted hazard ratios (HRs) for CVD in the moderately controlled group and poorly controlled group were 2.24 (95% confidence interval [CI]: 1.66–3.02) and 3.09 (95% CI: 2.04–4.68), respectively. The adjusted HRs for all-cause mortality in these two groups were 1.53 (1.15–2.04) and 2.65 (1.79–3.92), respectively. Conclusions We observed an inverse relationship between the degree of risk factor control and the risk of CVD and all-cause mortality in young adults, emphasizing the importance of actively controlling more risk factors in early life.